PH-responsive Ag2S nanodots loaded with heat shock protein 70 inhibitor for photoacoustic imaging-guided photothermal cancer therapy. (1st October 2020) - Zhong, Yaping; Zou, Yibiao; Liu, Lingyan; Li, Ruohan; Xue, Fengfeng; Yi, Tao
Abstract: Heat-treated cancer cells have thermo-resistance due to the up-regulated levels of heat shock proteins (HSP) resulting in low therapeutic efficiency and ineffective ablation of tumors. In this work, we report pH-responsive Ag2 S nanodots (Ag2 S NDs) loaded with HSP70 inhibitor (QE-PEG-Ag2 S) for enhanced photothermal cancer therapy. QE-PEG-Ag2 S was easily prepared via self-assembly of hydrophobic Ag2 S NDs, amphiphilic pH-responsive PEG5k -PAE10k polymer, and an HSP70 inhibitor quercetin (QE). QE-PEG-Ag2 S has ideal water-solubility and biocompatibility, can rapidly enter cells, and preferentially accumulate in cell lysosomes. The slightly acidic environment of tumor cells and the acidity of lysosomes as well as the high temperature generated by photothermal therapy under irradiation of NIR light (808 nm) promote the release of the inhibitor molecules to reduce the heat resistance of cancer cells and improve the in vivo photothermal therapy efficiency. Moreover, QE-PEG-Ag2 S has good photoacoustic imaging (PAI) ability; this QE-PEG-Ag2 S concentration dependent signal can precisely follow the accumulation of the nanomaterials in tumors and dictate the correct time for light therapy. As a result, QE-PEG-Ag2 S achieved complete tumor ablation effect with no recurrence when only irradiated with NIR light for 10 min. This approach offers a new approach for the theranostic applications of Ag2 S NDs. Statement of Significance: In this work, pH-responsive Ag2 S nanodots loaded with the heat shock protein inhibitor for enhanced photothermal cancer therapy have been simply prepared via self-assembly process. This nanoagent possesses ideal water-solubility and biocompatibility, can rapidly enter cells, and preferentially accumulate in cell lysosomes. The acidic environment of tumor cells and the acidity of lysosomes, as well as the high temperature generated by photothermal therapy under irradiation of NIR light promote the release of the inhibitor molecules from the nanoagent to improve the in vivo photothermal therapy efficiency. Moreover, the photoacoustic imaging (PAI) of the nanoagent can precisely follow the accumulation of the nanomaterials in tumors and dictate the light therapy time to guarantee the complete tumor ablation effect with no recurrence. Graphical abstract: Image, graphical abstract